Temporal Trends and Outcomes Among Patients Admitted for Immune‐Related Adverse Events: A Single‐Center Retrospective Cohort Study from 2011 to 2018. (31st March 2021) - Molina, Gabriel E.; Zubiri, Leyre; Cohen, Justine V.; Durbin, Sienna M.; Petrillo, Laura; Allen, Ian M.; Murciano‐Goroff, Yonina R.; Dougan, Michael; Thomas, Molly F.; Faje, Alexander T.; Rengarajan, Michelle; Guidon, Amanda C.; et al.
Abstract: Background: The aim of this study was to characterize severe immune‐related adverse events (irAEs) seen among hospitalized patients and to examine risk factors for irAE admissions and clinically relevant outcomes, including length of stay, immune checkpoint inhibitor (ICI) discontinuation, readmission, and death. Methods: Patients who received ICI therapy (ipilimumab, pembrolizumab, nivolumab, atezolizumab, durvalumab, avelumab, or any ICI combination) at Massachusetts General Hospital (MGH) and were hospitalized at MGH following ICI initiation between January 1, 2011, and October 24, 2018, were identified using pharmacy and hospital admission databases. Medical records of all irAE admissions were reviewed, and specialist review with defined criteria was performed. Demographic data, relevant clinical history (malignancy type and most recent ICI regimen), and key admission characteristics, including dates of admission and discharge, immunosuppressive management, ICI discontinuation, readmission, and death, were collected. Results: In total, 450 admissions were classified as irAE admissions and represent the study's cohort. Alongside the increasing use of ICIs at our institution, the number of patients admitted to MGH for irAEs has gradually increased every year from 9 in 2011 to 92 in 2018. The hospitalization rate per ICI recipient has declined over that same time period (25.0% in 2011 to 8.5% in 2018). The most common toxicities leading to hospitalization in our cohort were gastrointestinal (30.7%; n = 138), pulmonary (15.8%; n = 71), hepatic (14.2%; n = 64), endocrine (12.2%; n = 55), neurologic (8.4%; n = 38), cardiac (6.7%; n = 30), and dermatologic (4.4%; n = 20). Multivariable logistic regression revealed statistically significant increases in irAE admission risk for CTLA‐4 monotherapy recipients (odds ratio [OR], 2.02; p < .001) and CTLA‐4 plus PD‐1 combination therapy recipients (OR, 1.88; p < .001), relative to PD‐1/PD‐L1 monotherapy recipients, and patients with multiple toxicity had a 5‐fold increase in inpatient mortality. Conclusion: This study illustrates that cancer centers must be prepared to manage a wide variety of irAE types and that CTLA‐4 and combination ICI regimens are more likely to cause irAE admissions, and earlier. In addition, admissions for patients with multi‐organ involvement is common and those patients are at highest risk of inpatient mortality. Implications for Practice: The number of patients admitted to Massachusetts General Hospital for immune‐related adverse events (irAEs) has gradually increased every year and the most common admissions are for gastrointestinal (30.7%), pulmonary (15/8%), and hepatic (14.2%) events. Readmission rates are high (29% at 30 days, 49% at 180 days) and 64.2% have to permanently discontinue immune checkpoint inhibitor therapy. Importantly, multiple concurrent toxicities were seen in 21.6% (97/450) of irAE admissions and these patients have a fivefold increased risk of inpatient death. Abstract : Real‐world immune‐related adverse events (irAE) studies have been hampered by the relatively recent introduction of immune checkpoint inhibitor therapy. This article characterizes severe irAEs among hospitalized patients and examines risk factors for irAE admissions and clinically relevant outcomes.